2008
DOI: 10.1016/j.jada.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Grains Are Similarly Categorized by 8- to 13-Year-Old Children

Abstract: This study assessed how 8-to 13-year-old children categorized and labeled grain foods and how these categories and labels were influenced by child characteristics. The main hypotheses were that children categorized foods in consistent ways and these food categories differed from the professional food categories. A set of 71 cards with pictures and names of grain foods from eight professionally denned food groups was sorted by each child into piles of similar foods. There were 149 8-to 13-year-old children (133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The researchers identified the type of categories formed, based on the product characteristics and participants' comments about the products and the groups. The type of food categories were in accordance with the classification of food categories from Beltran et al (2008a): food characteristics (referring to the concrete characterization of the foods, like form, color, etc. ), taxonomic (referring to the common properties, like the type of food class), script (referring to the same role in a routine or event), and evaluative (referring to preferences, do not like/ do not buy).…”
Section: Procedures and Data-analysis Stepmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers identified the type of categories formed, based on the product characteristics and participants' comments about the products and the groups. The type of food categories were in accordance with the classification of food categories from Beltran et al (2008a): food characteristics (referring to the concrete characterization of the foods, like form, color, etc. ), taxonomic (referring to the common properties, like the type of food class), script (referring to the same role in a routine or event), and evaluative (referring to preferences, do not like/ do not buy).…”
Section: Procedures and Data-analysis Stepmentioning
confidence: 99%
“…on crossclassification by Ross and Murphy (1999), on children's development by Nguyen and Murphy (2003), and on family resemblance by Ward and Loken (1986). Categorization was also applied to identify food perceptions for improving dietary measures, education and communication (Beltran et al, 2008a(Beltran et al, , 2008b, and to study the effect of eating context (Blake, 2008;Blake et al, 2007).…”
Section: The Strong Taxonomic Categorization Of Meat Productsmentioning
confidence: 99%
“…Methods similar to those used in this study were applied to different groups of food items: mixed foods (19), fruit and vegetables (20), and grain foods (21). Inter study comparisons revealed Script and Taxonomic categories were also the most used in the other reports, but in the case of the Mixed dishes study, Specific Foods was the second most commonly used category (19).…”
Section: Discussionmentioning
confidence: 99%
“…To minimise possible sequence and fatigue effects, the sequence of card sort tasks was randomly assigned. Card sort 1 was composed of diverse single food items (26) , card sort 2 contained mixed food items (27) , card sort 3 included only fruit, card sort 4 included only vegetables, which were analysed for this manuscript and card sort 5 contained diverse grains and cereals (28) . Children were scheduled to perform the card sort activities across two days, except for those with an early morning appointment who had time to finish all the activities in one day.…”
Section: Methodsmentioning
confidence: 99%